Stunting Prevention Program in Indonesia: A SYSTEMATIC REVIEW: PROGRAM PENCEGAHAN STUNTING DI INDONESIA: A SYSTEMATIC REVIEW - Rahmi Fitri J; Najla Huljannah; Thinni Nurul Rochmah (Universitas Airlangga, 2022)
Stunting or chronic undernutrition is a consequence of a lack of nutrition for a long time. Stunting is still a main isu in developing countries such as Indonesia. According to SSGBI 2021, the prevalence of stunting in Indonesia was decreased from 2019 to 2021 that is 27,67% to 24,4%. Government has many programs to decrease stunting. Thus, research that can present facts comprehensively about stunting prevention program is needed to make policies regarding the precise and efficient program. The research aims to identify stunting prevention program in Indonesia. This research used a systematic review method arranged based on Preferred Reporting Items for Systematic Reviews and MetaAnalyzes (PRISMA). Five databases are used for searching articles that are PubMed, Google Scholar, Portal Garuda, Perpustakaan Nasional (Perpusnas) Indonesia, and ScienceDirect. Research inclusion criteria are articles were published from 2011 to 2020 with the population in Indonesia. For articles assessing quality we used The Joanna Briggs Institute (JBI) Critical Appraisal. Form 15 articles we found that effective program for preventing stunting is nutrition education for influential parties (cadre, children’s mother, pregnant women, and mother to be), establishing a study group for children’s mother, and supplementary feeding for children. Stunting prevention program must be paying attention to input and process aspects for better outputs and must involve all parties from children’s mothers to cross-sectoral.